166k views
1 vote
The product of -a^2b^2c^2(a+b-c)

User Ntshetty
by
6.3k points

2 Answers

6 votes

=−a3b2c2−a2b3c2+a2b2c is the answer


User Eriaac
by
5.6k points
1 vote

Answer: The required product is
-a^3b^2c^2-a^2b^3c^2+a^2b^2c^3.

Step-by-step explanation: We are given to find the following product :


P=-a^2b^2c^2(a+b-c)~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)

We will be using the following property of exponents to find the give product :


x^a* x^b=x^(a+b).

The product (i) can be calculated as follows :


P\\\\=-a^2b^2c^2(a+b-c)\\\\=-a^(2+1)b^2c^2-a^2b^(2+1)c^2+a^2b^2c^(2+1)\\\\=-a^3b^2c^2-a^2b^3c^2+a^2b^2c^3.

Thus, the required product is
-a^3b^2c^2-a^2b^3c^2+a^2b^2c^3.

User Jeff Tsui
by
6.3k points